EMPOWERING NEURODIVERGENT LEARNERS IN INCLUSIVE CLASSROOMS: A CULTURALLY RESPONSIVE TEACHING (CRT) PERSPECTIVE - Manasi Panwar; Pushp Lata (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The global commitment to inclusive education under the United Nations Sustainable Development Goal (SDG 4) aims to accommodate the diverse learning needs of neurodivergent learners comprehensively. Conventional teaching methods often underserved the unique learning requirements of neurodivergent learners, such as those with dyslexia. The study examines the impact of Culturally Responsive Teaching (CRT) as an instructional approach, emphasizing the use of culturally relevant learning materials, differentiated and flexible instruction, visual cues, and social emotional learning (SEL) interventions on the academic, behavioral, and social-emotional development of dyslexic learners. Employing a qualitative research design, the study draws on data from classroom observations and semi-structured interviews with teachers and parents to explore how CRT strategies influence learner development. The findings underscore the positive impact of the aforementioned CRT strategies on academic achievements, confidence-building, learner engagement, peer relationships, and socio-emotional growth among dyslexic learners. The implications of the study extend to linking CRT strategies with the broader goals of SDG 4, promoting an equitable and inclusive educational landscape empowering dyslexic learners.